2008
DOI: 10.1161/01.res.0000326772.76822.7a
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase Delays Neutrophil Apoptosis Through CD11b/CD18 Integrins and Prolongs Inflammation

Abstract: Abstract-Polymorphonuclear neutrophil granulocytes have a central role in innate immunity and their programmed cell death and removal are critical for efficient resolution of acute inflammation. Myeloperoxidase (MPO), a heme protein abundantly expressed in neutrophils, is generally associated with killing of bacteria and oxidative tissue injury. Because MPO also binds to neutrophils, we investigated whether MPO could affect the lifespan of neutrophils. Here, we report that MPO independent of its catalytic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
170
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(188 citation statements)
references
References 48 publications
9
170
0
9
Order By: Relevance
“…11 Interleukin-18 is known to activate neutrophil function. Netea et al showed that neutralization of IL-18 reduced LPS-induced accumulation of neutrophils in the lung and liver.…”
Section: Discussionmentioning
confidence: 99%
“…11 Interleukin-18 is known to activate neutrophil function. Netea et al showed that neutralization of IL-18 reduced LPS-induced accumulation of neutrophils in the lung and liver.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we further examined the effects of MPO on glial cells using purified MPO. Several reports 15 have shown that purified MPO has its activity when added to cultured cells or animals. Although relatively little is known of the amounts of MPO in the CNS, the plasma levels of MPO in patients with vascular diseases have been described.…”
Section: Discussionmentioning
confidence: 99%
“…MPO has been closely involved in stimulating mitogen-activated protein kinase activity, cell growth, and protease activity, thereby influencing the immune responses and the progression of several inflammation-associated diseases. 10,[15][16][17][18][19] Until recently, phagocytic blood cells were thought to be the only cellular sources of MPO. However, recent studies 18,20,21 have shown that several cell types, including neuronal cells, express MPO under certain pathological conditions.…”
mentioning
confidence: 99%
“…82 MPO may further promote survival of neutrophils by ligation of CD11b/CD18, thereby prolonging inflammation. 131 In addition, a recent study points at the importance of neutrophils as a source of reactive oxygen species in vulnerable plaques. 30 Matrix-degrading proteases participate in the degradation of the basement membrane.…”
Section: Neutrophil-derived Reactive Species and Proteases May Promotmentioning
confidence: 99%